A Creative Information System Based on the SCAMPER Technique - Lopes, Rute (2022)
Lopes, R., Malta, P., Mamede, H., & Santos, V. (2020). A Creative Information System Based on the SCAMPER Technique. In M. Themistocleous, M. Papadaki, & M. M. Kamal (Eds.), Information Systems: 17th European, Mediterranean, and Middle Eastern Conference, EMCIS 2020, Proceedings (pp. 595-606). (Lecture Notes in Business Information Processing; Vol. 402). Springer Science and Business Media Deutschland GmbH. https://doi.org/10.1007/978-3-030-63396-7_40